1,8-Naphthalimide-Based Multifunctional Compounds as Cu2+ Probes, Lysosome Staining Agents, and Non-viral Vectors - Gao, Yong-Guang; Liu, Fen-Li; Patil, Suryaji; Li, Di-Jie; Qadir, Abdul; Lin, Xiao; Tian, Ye; Li, Yu; Qian, Ai-Rong (Frontiers in Chemistry, 2019)
A series of multifunctional compounds (MFCs) 1a-1d based on 1,8-naphthalimide moiety were designed and synthesized. Due to the good fluorescence property and nucleic acids binding ability of 1,8-naphthalimide, these MFCs were applied in Cu2+ ions recognition, lysosome staining as well as RNA delivery. It was found that these MFCs exhibited highly selective fluorescence turn-off for Cu2+ in aqueous solution. The fluorescence emission of 1a-1d was quenched by a factor of 116-fold, 20-fold, 12-fold, and 14-fold respectively in the presence of Cu2+ ions. Most importantly, 1a-Cu and 1b-Cu could be used as imaging reagents for detection of lysosome in live human cervical cancer cells (HeLa) using fluorescence microscope. Furthermore, in order to evaluate RNA delivery ability of 1a-1d, cellular uptake experiment was performed in HeLa, HepG2, U2Os and MC3T3-E1 cells. The results showed that all the materials could deliver Cy5-labbled RNA into target cells. Among of them, compound 1d modified with long hydrophobic chain exhibited the best RNA delivery ability in four tested cell lines, and the performance was far better than lipofectamine 2000 and 25 kDa PEI, indicating the potential application in non-viral vectors.